EVALUASI PENGGUNAAN ANTIBIOTIK PADA PASIEN INFEKSI SALURAN PERNAFASAN DI PUSKESMAS RAWAT JALAN KECAMATAN SIULAK MUKAI KABUPATEN KERINCI TAHUN 2018 - Rasmala Dewi; Deny Sutrisno; Andral Pramirta (Fakultas Farmasi UMI, 2020)
Respiratory infections a major health problem that is commonly found in Indonesia. The height prevalence of respiratory tract infections and their effects have consequences high consumption of over the counter medicines and antibiotics. This research aims to evaluating the use of antibiotics which includes the right patient, the right indication of the drug, the right dose, and the interaction of the drug in patients with respiratory infections in outpatien health centers in the district of Siulak Mukai in Kerinci District in 2018. This study is a observational research is descriptive in nature by collecting data on records medical outpatients retrospectively according to age inclusion criteria 25 years, patients with a diagnosis of respiratory tract infections in outpatient health centers in the district of Siulak Mukai, Kerinci Regency in 2018, complete medical record data and analyzed with the guidelines of Pharmaceutucal Care 2005 with descriptive methods. The results of evaluating the use of antibiotics in patients with respiratory tract infections in outpatient clinics in the district of Siulak Mukai in Kerinci Regency in 2018, showed that 100 % apporopriate treaments, as well as the incidence of antibiotic drug interactions by 2 events.